2016
DOI: 10.1108/jsm-07-2014-0263
|View full text |Cite
|
Sign up to set email alerts
|

Examining customer evaluations across different self-service technologies

Abstract: Purpose This study aims to examine the influence of different self-service technologies (SSTs) on customer satisfaction with and continued usage of SSTs. Specifically, it compares an interactive voice response (IVR) SST and an online SST from the same provider to assess how to manage these parallel SSTs. Design/methodology/approach A tracking study was used, beginning with a survey of n = 957 SST users to test a model pertaining to SST satisfaction across IVR and online SSTs. These SST users were then tracke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 79 publications
8
60
0
1
Order By: Relevance
“…Consequently, this creates a scenario where customers' satisfaction determines the usability of the SST in future activities (Sierra and McQuitty, 2005;Sierra et al, 2009;Åkesson et al, 2014;Robertson et al, 2016). Past study found that reliability, user-friendly, enjoyment, and perceived control of the service associated positively with customer satisfaction for online and interactive voice response (IVR) (Robertson et al, 2016). However, here again, the evaluated SSTs provided the same services.…”
Section: Literature Review and Hypothesesmentioning
confidence: 87%
See 4 more Smart Citations
“…Consequently, this creates a scenario where customers' satisfaction determines the usability of the SST in future activities (Sierra and McQuitty, 2005;Sierra et al, 2009;Åkesson et al, 2014;Robertson et al, 2016). Past study found that reliability, user-friendly, enjoyment, and perceived control of the service associated positively with customer satisfaction for online and interactive voice response (IVR) (Robertson et al, 2016). However, here again, the evaluated SSTs provided the same services.…”
Section: Literature Review and Hypothesesmentioning
confidence: 87%
“…According to Curran and Meuter (2005), "self" indicates a customers' willingness to participate in the process during service encounter. Thus, customers' performance creates value for an organization's SSTs (Dabholkar,1990;Xue et al, 2005;Robertson et al, 2016). Therefore, during a service encounter, customers likely become an organization's "partial employees" (Bettencourt, 1997;Xue et al, 2005), i.e., customers provisionally involve with SSTs during service production by contributing some activities, such as effort.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations